Número de folíolos no enraizamento de estacas herbáceas de lichieira - Alves, Ediane Conceição; Guimarães, João Emmanuel Ribeiro [UNESP]; Franco, Camila Kauffmann Becaro [UNESP]; Martins, Antonio Baldo Geraldo [UNESP] (FapUNIFESP (SciELO), 2016)
Lychee is one of the most popular exotic fruits in Brazil, and has both in natura and industrial potential. The objective of the present study was to evaluate the influence of the number of leaflets on lychee herbaceous cuttings treated with the indolebutyric acid (1000mg L-1). The experimental design was completely randomized, with 4 replications and 10 cuttings per experimental plot. Treatments consisted of cuttings with zero (0), one (1), two (2), three (3), and four (4) leaflets. After 180 days, the rooting and survival percentages and the number and length of roots were evaluated. The data were subjected to polynomial regression analysis. The increase in the number of leaflets was advantageus for all studied variables, with an increase in the survival, rooting of cuttings, and number and length of roots. The herbaceous cuttings of lychee tree are viable, provided that at least four leaflets remain in the herbaceous cutting.
Number of leaflets on rooting of lychee herbaceous cuttings
Keywords: Cutting; Leaflets; Litchi chinensis; Propagation